The Effectiveness of Teaching Writing Invitation Through Carousel Feedback at Vocational High School Students - Dessy Ayu Ardini; Annisa Rahmasari; Wiratno Wiratno (Journal of Development Research, 2023)
The purpose of this study is to know whether there is significant difference on English Grammar achievement of the first year Vocational School students taught using Carousel Feedback and those taught using Grammar Translation Method. This research used X-TKR 2 class as the experiment class and X-TKR 1 class as the control class. To measure the effectiveness of the specific learning objective as the instruments, the researchers used essay tests consisted of 10 items. Considering that the researchers are applying Non-Randomized Pretest-Posttest control group design, the result of the study was analyzed using ANCOVA formula and computed using SPSS version 22.0. It shows that there is significant difference on English Writing achievement between students taught using Carousel Feedback and those who taught using Grammar Translation Method on teaching writing invitation letter.